Plasmonic high gain graphene-based antenna array design for ultra wide band terahertz applications - Rasha H. Mahdi; Hussein A. Abdulnabi; Ahlam Alsudani (Institute of Advanced Engineering and Science, 2022)
Graphene, which consists of one atomic slide made from the Carbon, and it utilized in various of the implementations like the chemical, the thermal, the mechanical, and the electrical. In this research article, a high gain plasmonic antenna array is proposed for the utilizations of the terahertz (THz) regime on the basis of the graphene material. Also, the surface plasmon polariton (SPP) waves phenomena which emerged at THz in graphene are demonstrated the suggested antenna is composed of (4*6) graphene patches and a graphene Nano ribbon feeder to excite the patches deposed on the lumina layer. The simulated antenna was designed and investigated via the utilizing of the CST software. The obtained outcomes show that the antenna operation frequency bands covered a large band at the 2.6-10, 2.28-2.5, 1.87-2.14, and 1.4-1.6 THz with an S11 ≤ -10 dB and an expedient antenna gain in the operating frequency ranges.